Kaleidoscopical graphs and semigroups - K. D. Protasova (Математичні Студії)
We give a semigroup characterization of kaleidoscopical graphs. A connected graph Г (considered as a metric space with the path metric) is called kaleidoscopical if there is a vertex coloring of Г which is bijective on each unit ball.